The liberty of strangers : making the American nation - King, Desmond S. (Oxford University Press, 2005)
Spanning the entire twentieth century and encompassing immigration policies, the nationalistic fallout from both world wars, the civil rights movement, and nation-building efforts in the postcolonial era, this work advances a major interpretation of American nationalism and the future prospects for diverse democracies.